Progressed learners as a burden for teachers: A case of selected participants from Limpopo Province, South Africa - Mbusiseni Celimpilo Dube (Interdisciplinary Journal of Education Research)
This study examines teachers' perspectives on the academic performance of progressed learners. The research adopted an interpretive paradigm aligned with qualitative methods, using purposive sampling to engage 10 Grade 12 teachers through semi-structured interviews. Thematic analysis of the data revealed that progressed learners are often segregated, struggle with understanding English as a Language of Learning and Teaching, find it difficult to cope with the workload in Grade 12, and most come from child-headed families. The study concludes that most teachers are dissatisfied with progressed learners because they did not meet the requirements for progression, and if they perform poorly, teachers feel they are to blame. It is recommended that teachers be trained and equipped with the necessary teaching strategies for handling progressed learners, particularly those who progressed after meeting the progression requirements. The Department of Basic Education (DBE) should monitor the progress of these learners and obtain regular feedback from teachers regarding their academic performance. This can help identify cases where both teachers and learners need support. Teachers should not compromise the quality of education by teaching in the learners' vernacular; instead, they should teach in English, as assessments are conducted in English. The School-Based Support Teams (SBSTs) should identify progressed learners who are heading families and seek support for them from relevant individuals or departments. Parents and teachers should sign a memorandum of understanding outlining their roles in supporting progressed learners. Additionally, progressed learners should be taught skills to help them cope with the pressures of the new grade.